Techno-economic assessment of scale-up of bio-flocculant extraction and production by using okra as biomass feedstock - Lee, Chai Siah; Chong, Mei Fong; Binner, Eleanor; Gomes, Rachel L.; Robinson, John P. (Elsevier, 2018)
This paper reports a techno-economic assessment for industrial scale bio-flocculant production with okra as biomass feedstock. The sludge dewatering ability of the bio-flocculant was evaluated prior to economic analysis. Several optimisation strategies were investigated in order to lower the bio-flocculant production cost. The results showed that continuous mode microwave extraction was more economically beneficial than conventional extraction in batch and continuous modes. Sensitivity analysis revealed that the production cost was significantly affected by annual production and extract yield, and moderately influenced by raw material price. The optimised scheme for bio-flocculant production was continuous mode microwave extraction at 90° C, a residence time of 10 minutes, a water loading of 3.5 w/w and production rate of 220 tonnes per year. The economic assessment showed that the gross margin was positive, return on investment was in the expected range of 20 to 30% and payback time was within 5 years.